2015
DOI: 10.1542/peds.2014-3399
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of a National Newborn Screening Program for Biotinidase Deficiency

Abstract: BACKGROUND AND OBJECTIVES: There are conflicting views as to whether testing for biotinidase deficiency (BD) ought to be incorporated into universal newborn screening (NBS) programs. The aim of this study was to evaluate the cost-effectiveness of adding BD to the panel of conditions currently screened under the national NBS program in Spain. METHODS:We used information from the regional NBS program for BD that has been in place in the Spanish region of Galicia since 1987. These data, along with other sources, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 42 publications
0
13
1
Order By: Relevance
“…17 Only 7% of these (~1:50 000) neonates had a profound deficiency, compared with 1:137 401 reported by Wolf. The large difference between the worldwide survey and the incidence found in our study and others 16,[20][21][22][23][24][25][26][27][28] is likely due to considerable variation in the occurrence of this disorder across countries. Therefore, it is important for each country to study the incidence of biotinidase deficiency.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…17 Only 7% of these (~1:50 000) neonates had a profound deficiency, compared with 1:137 401 reported by Wolf. The large difference between the worldwide survey and the incidence found in our study and others 16,[20][21][22][23][24][25][26][27][28] is likely due to considerable variation in the occurrence of this disorder across countries. Therefore, it is important for each country to study the incidence of biotinidase deficiency.…”
Section: Discussioncontrasting
confidence: 80%
“…17 More recent publications, however, indicate that the incidence of biotinidase deficiency ranges from 1:4500 to 1:62 500 in countries that screen for this disorder (eg, Brazil, the USA, Belgium, Germany and Greece). 16,[20][21][22][23][24][25][26][27][28] Our study shows that, in the Netherlands, 1 in 6100 to 1 in 8200 neonates had partial or profound biotinidase deficiency. 17 Only 7% of these (~1:50 000) neonates had a profound deficiency, compared with 1:137 401 reported by Wolf.…”
Section: Discussionmentioning
confidence: 53%
“…51 Several studies have shown the cost-effectiveness of screening for both profound and partial biotinidase deficiency. [52][53][54] Currently, all newborn screening programs in the United States and more than 30 other countries screen for biotinidase deficiency, with multiple recent studies suggesting that additional countries are considering incorporation of biotinidase deficiency into their newborn screening programs. [55][56][57][58][59][60] Historically, the screening method used was a colorimetric assay of biotinidase activity measured in dried blood spots, and states have individually established their own screening cutoffs and rescreening or follow-up protocols.…”
Section: Newborn Screening For Biotinidase Deficiencymentioning
confidence: 99%
“…There have been several studies that have addressed this issue, and they have all agreed that newborn screening for biotinidase deficiency is cost-effective [62][63][64].…”
Section: Newborn Screening For Biotinidase Deficiency Is Not For Evermentioning
confidence: 99%